2019
DOI: 10.17511/ijmrr.2019.i04.05
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic control amongst diabetic subjects on insulin therapy: Still off target!

Abstract: Introduction:Prevalence of diabetes is increasing worldwide. Good glycemic control is essential for prevention of complications of diabetes. Despite of availability of multiple medications, it is difficult to achieve good glycemic control. Insulin therapy is considered to be the best option available for attaining glycemic control. But, whether insulin therapy has achieved it is an important question to be addressed. Objective: To assess the glycemic control in subjects with diabetes on insulin therapy. Materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
(9 reference statements)
0
3
1
Order By: Relevance
“…Several studies have demonstrated that patients with type 2 diabetes have a gap in knowledge, a negative attitude and incorrect practices regarding insulin therapy 15 18–22. However, the present study’s findings showed that patients with type 2 diabetes receiving insulin therapy have adequate knowledge, positive attitudes and correct practices regarding their insulin therapy.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…Several studies have demonstrated that patients with type 2 diabetes have a gap in knowledge, a negative attitude and incorrect practices regarding insulin therapy 15 18–22. However, the present study’s findings showed that patients with type 2 diabetes receiving insulin therapy have adequate knowledge, positive attitudes and correct practices regarding their insulin therapy.…”
Section: Discussioncontrasting
confidence: 82%
“…The present study participants (42%) reported that injecting insulin is painful. Similarly, Shetty et al 25 found that 49.9% of their participants (n=448) felt that insulin injections are painful. Furthermore, Fu et al 17 found that 66.9% of their study participants (n=306) had a negative attitude towards insulin therapy as injecting insulin is painful.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In this way, it is sought to mimic pancreatic physiological function and thus achieve better results (American Diabetes Association Professional Practice Committee, 2022). However, despite being the "gold standard" in the treatment of T1D and T2D with advanced beta secretory failure, exogenous insulin therapy has been associated with adverse effects such as weight gain, lipoatrophy, hyperlipotrophy, skin infections, hypoglycemia (Demir et al, 2022;Guarneri and Hoffman, 2022;Amiel, 2021), and even therapeutic failure in a considerable percentage of patients (Al-Qerem et al, 2022;Sherwood et al, 2020;Shetty and Ramachandrappa, 2019;Alzaheb and Altemani, 2018). As a result, efficient therapeutic strategies have been developed in recent decades to effectively control these disorders and restore endogenous insulin production (Posselt et al, 2010).…”
Section: Introductionmentioning
confidence: 99%